1991
DOI: 10.1002/j.1460-2075.1991.tb04910.x
|View full text |Cite
|
Sign up to set email alerts
|

DNA template effect on RNA splicing: two copies of the same gene in the same nucleus are processed differently.

Abstract: Many cellular and viral genes are parts of complex transcription units containing multiple splicing choices. During the course of an adenoviral replicative cycle, different spliced versions of a single gene predominate, depending on the stage of infection. This is true for several adenoviral genes. In this paper we show for the viral E1B transcription unit that splice site usage regulates this process. The change in alternative splicing in this system does not depend on the sequence of the transcribed genes. N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

1993
1993
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 52 publications
1
23
0
Order By: Relevance
“…Consistent with this, NM22 coimmunoprecipitated a higher level of B3-reactive pol IIo compared with NM4 (compare lanes 6 and 7), corresponding to a40-50% of that present in the total extract (compare lanes 4 and 7). Immunoprecipitation of B3-reactive pol IIo by these mAbs appeared to occur through the recognition of SR proteins and not by direct binding to pol IIo, as neither NM22 nor NM4 were reactive with pol IIo in the preparation of purified polymerase (data not shown (31,32). This model is similar to a previous proposal (33) and is also supported by the recent identification of four novel proteins containing SR domains that interact with the CTD of pol 11 (34).…”
Section: Resultssupporting
confidence: 81%
“…Consistent with this, NM22 coimmunoprecipitated a higher level of B3-reactive pol IIo compared with NM4 (compare lanes 6 and 7), corresponding to a40-50% of that present in the total extract (compare lanes 4 and 7). Immunoprecipitation of B3-reactive pol IIo by these mAbs appeared to occur through the recognition of SR proteins and not by direct binding to pol IIo, as neither NM22 nor NM4 were reactive with pol IIo in the preparation of purified polymerase (data not shown (31,32). This model is similar to a previous proposal (33) and is also supported by the recent identification of four novel proteins containing SR domains that interact with the CTD of pol 11 (34).…”
Section: Resultssupporting
confidence: 81%
“…In contrast, previous reports presented evidence for a direct effect of the SV40 replication origin in activating the SV40 late promoter (23). Results from adenoviruses (24,25) indicated cis-acting template effects on transcriptional control and posttranscriptional processing. A systematic study of a cis effect of DNA replication on polyoma late gene activation has not yet been reported.…”
mentioning
confidence: 62%
“…As DNA replication has been suggested to influence the gene expression of several animal viruses in cis (17,(23)(24)(25), we carried out cotransfection experiments with wild-type virus and a marked replication-incompetent genome, oriA-M (Fig. 2).…”
Section: Methodsmentioning
confidence: 99%
“…It has also been suggested that nuclear compartmentalization is an epigenetic mechanism (Riggs and Porter 1996), and, therefore, the epigenetic factors may play a role in the further processing of mRNAs. At least two experimental studies suggested the role of DNA template-based (cis) factors but not cytoplasmatic (trans) factors in alternative splicing (Adami andBabiss 1991, Hayward et al 1998). The first study demonstrated that different spliced versions of the E1B gene may originate from late and early adenoviral genomes which co-existed in the same cell.…”
Section: Epigenetic Interpretation Of the Drd3 Findings In Sczmentioning
confidence: 99%